1997
DOI: 10.1007/s002340050377
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and early postoperative colour Doppler sonography after carotid artery reconstruction: follow-up of technical defects

Abstract: We studied 50 patients with intraoperative colour-coded Doppler sonography (CCDS) after carotid artery reconstruction. Technical defects could be detected in 19 cases (38 %): residual plaques in 9, flaps in 8 and strictures in 2. In 9 cases (18 %) the carotid endarterectomy was revised. One residual plaque and one residual stricture caused thrombosis at the operative site a few hours postoperatively. One of the patients with residual plaques developed a high-grade stenosis within the follow-up period. Of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Completion angiography, intraoperative duplex scanning and angioscopy have been used individually or in combination to assess the technical success of CE, although duplex scanning seems to play a greater role nowadays due to its overall feasibility and efficacy (11). It has been suggested that abnormalities left uncorrected at the time of CE may contribute to restenosis, although small intimal flaps probably do not matter (24). Other residual lesions that may be present post‐CE include atheroma, intraluminal thrombi, kinks and vein patch irregularities.…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…Completion angiography, intraoperative duplex scanning and angioscopy have been used individually or in combination to assess the technical success of CE, although duplex scanning seems to play a greater role nowadays due to its overall feasibility and efficacy (11). It has been suggested that abnormalities left uncorrected at the time of CE may contribute to restenosis, although small intimal flaps probably do not matter (24). Other residual lesions that may be present post‐CE include atheroma, intraluminal thrombi, kinks and vein patch irregularities.…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…Ultimately, 9 studies were eligible and included in the quantitative analysis. [6][7][8][9][21][22][23][24][25] The summarizing PRISMA flow chart is outlined in Fig. 4.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Auch bei diesen Rekonstruktionen finden sich in ca. 10-30% morphologische Läsionen oder hämodynamische Störungen (Turbulenzen), die hypothetisch einen Insult verursachen oder mit verursachen können [4,11,22,38]. Rekonstruktionen, die für die Peripherie akzeptiert werden können, erzeugen an der zerebralen Strombahn u. U. neurologische Ereignisse und sind daher nicht zu tolerieren.…”
Section: Irregularitäten Der Rekonstruktionunclassified
“…In der Literatur werden residuelle Läsi-onen oder hämodynamische Probleme in 2-30% angeschuldigt, die in 2-12% zu einer sofortigen Reinterventionen führten, wenn ein intraoperatives Qualitätsmoni-toring während der Karotisrekonstruktion vorgenommen wurde [2,4,11,14,15,18,20,22,27,28,32,38].…”
Section: > Erfahrung Und Fallzahl Nehmen Einfluss Auf Das Ergebnis Deunclassified